The novel outer membrane protein from OprD/Occ family is associated with hypervirulence of carbapenem resistant Acinetobacter baumannii ST2/KL22. Issue 1 (1st January 2021) - Hua, Mingxi; Liu, Jingyuan; Du, Pengcheng; Liu, Xinzhe; Li, Min; Wang, Huizhu; Chen, Chen; Xu, Xinmin; Jiang, Yu; Wang, Yajie; Zeng, Hui; Li, Ang
ABSTRACT: Acinetobacter baumannii has become a major healthcare threat that causes nosocomial infections, especially in critically ill patients. The spread of carbapenem-resistant A. baumannii (CRAB) strains has long been a clinical concern. It is important to study the epidemiology and virulence characteristics of different CRAB isolates in order to tailor infection prevention and antibiotic prescribing. In this study, a total of 71 CRAB isolates were collected in the hospital, and clinical characteristics of infections were analyzed. The genomic characteristics and phylogenetic relationships were elucidated based on genome sequencing and analysis. The isolates were assigned to three sequence types (STs, Pasteur) and nine capsular polysaccharide (KL) types, among which ST2/KL22 was the most prevalent CRAB in the hospital. Even though all the ST2/KL22 isolates contained the same reported virulence genes, one specific clade of ST2/KL22 showed more pathogenic in mouse infection model. Complete genomic analysis revealed differences at the oprD locus between the low- and high-virulent isolates. More specifically, a premature stop codon in the low-virulence strains resulted in truncated OprD expression. By evaluating pathogenicity in C57BL/6 J mice, knock-out of oprD in high-virulent isolate resulted in virulence attenuation, and complementing the avirulent strain with full-length oprD from high-virulent isolate enhanced virulence of the former. The oprD gene may be associated with the enhanced virulence of the specific ST2/KL22 clone, which provides a potential molecular marker for screening the hypervirulent A. baumannii strains.